2016
DOI: 10.5125/jkaoms.2016.42.4.182
|View full text |Cite
|
Sign up to set email alerts
|

Mini-plate removal in maxillofacial trauma patients during a five-year retrospective study

Abstract: ObjectivesThe purpose of this study was to analyze the incidence of indications for the removal of mini-plates over a five-year period in maxillofacial trauma patients.Materials and MethodsThe medical records of 530 patients who underwent treatment with mini-plate fixation after maxillofacial trauma were reviewed for a five-year period (May 2007 to May 2012). Patients were evaluated concerning the number of mini-plates removed, age and gender distributions, time between insertion and removal, indication for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
2
25
2
2
Order By: Relevance
“…The indication for removal is consequently more often a symptom in other studies, especially with respect to infection. In contrast, Park et al have reported patient demand as the main reason for removal; in their study, the surgeon did not recommend elective plate removal, and surgery was only performed because of patient request or symptoms [5]. The frequency of patient request averaged 16.7% in the present study increasing in the second postoperative year.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…The indication for removal is consequently more often a symptom in other studies, especially with respect to infection. In contrast, Park et al have reported patient demand as the main reason for removal; in their study, the surgeon did not recommend elective plate removal, and surgery was only performed because of patient request or symptoms [5]. The frequency of patient request averaged 16.7% in the present study increasing in the second postoperative year.…”
Section: Discussioncontrasting
confidence: 83%
“…Removal within a year or less after osteosynthesis is frequently reported [3,5,14,17,18]. The most common complication after osteosynthesis was hypesthesia in this study.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The rate of removal of miniplates has wide range in literature from 5% to 40% 11 and our current study has 7% of removal rate. Hyun-chun park et al 12 found patient's demand as the leading cause for plate removal whereas Rosenberg et al 13 in their study observed infection as the commonest cause for which plate exit had been done. In the current study 50% of miniplate removal was due to infection followed by implant exposure as the next reason for removal of miniplates.…”
Section: Discussionmentioning
confidence: 98%